ETNOPEDAGOGIK QADRIYATLAR ASOSIDA BO‘LAJAK O‘QITUVChILARDA AXLOQIY KO‘NIKMALARNI TAKOMILLAShTIRISh – IJTIMOIY-PEDAGOGIK ZARURIYAT - Pazilov, A.K. (SCIENCE and SOCIETY, 2025)
The article provides an assessment of the concept of ethnopedagogy from a scientific point of view and examines the socio-pedagogical necessity of improving the moral skills of future teachers based on ethnopedagogical values.